Analysis of Village Financial Planning in Towayu Village, Paguyaman Pantai District, Boalemo Regency - Hendrika Mahluk; Titin Dunggio; Sukrianto (Journal of Economic, Business, and Administration (JEBA), 2021)
The research objective was to determine the financial planning process in Towayu Village, Paguyaman Pantai District, Boalemo Regency. This type of research used in this research is a type of qualitative research with a descriptive approach. The descriptive approach of the researcher wants to describe or describe how village financial planning is in Towayu Village, Paguyaman Pantai District. The result of this research is that the draft RPJMDes will be discussed and agreed upon by the Village Head and BPD and then stipulated as a Village Regulation concerning the RPJMDes no later than 3 months after the elected Village Head is appointed. It is often found that the Towayu Village Government has not fully adjusted the actual RPJMDes flow to PERMENDAGRI No. 113 of 2014. Because those met in the field turned out that the preparation of the RPJMDes in the Towayu Village Government was only carried out towards the end of the year. This is a big problem and can even hinder all village activities, both development planning in the village, village empowerment 2) The Village Consultative Body (BPD) will hold deliberations in the framework of drafting RKPDes, and the results of the BPD deliberations serve as guidelines for the Village to compile a draft RKPDes and a list of RKPDes,